Acoustic telemetry system as a novel approach for evaluating the effective attraction of fish to artificial reefs - Lyu, Shaoliang; Lauden, Hagai Nsobi; Wang, Lifei; Chen, Guobao; Wang, Zhichao; Lin, Kun; Wang, Xuefeng (Frontiers in Marine Science, 2023)
In a view of the lack of an effective approach for evaluating the effectiveness of artificial reefs, two experiments were designed to attest the feasibility of acoustic telemetry, a rapidly developing method for tracking aquatic animals. Specifically, the first experiment was conducted to understand the deployment procedures of an acoustic telemetry system and determine the appropriate deployment of receivers′ spacing while the second experiment was conducted to quantify the site fidelity and habitat use of 11 reef fish in Fangchenggang artificial reefs area of China, northern South China Sea. The results indicated that the logistic regression model was a good way to predict the detection probability at different distances between the range test transmitter and receiver, with above 50% detection probability within 240 m and 80% detection probability within 110 m. The residency index (as a quantification of site fidelity) was 0.85 ± 0.24. 100% minimum convex polygon, 95% kernel utilization distribution, and 50% kernel utilization distribution (as a quantification of habitat use) were 34522.94 ± 35548.95 m2, 1467.52 ± 1619.05 m2, 236.01 ± 294.59 m2, respectively. High site fidelity and small spatial scale of habitat use for reef fish demonstrated that artificial reefs were an effective man-made structure to attract fish. Overall, this study confirms the feasibility of the acoustic telemetry system and suggests that it may be an effective approach for evaluating the effectiveness of artificial reefs.